BAURAN PEMASARAN (MARKETING MIX) PADA USAHA MIKRO KECIL MENENGAH (UMKM) CRAB FOOD MC DI KELURAHAN TELUK LERONG ULU KOTA SAMARINDA KALIMANTAN TIMUR - Idris, Muh Isram; Purnamasari, Elly; Ningsih, Etik Sulistiowati (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
This study aims to determine the application of the 7P marketing mix marketing mix to UMKM Crab Food MC, Teluk Lerong Ulu Village, Samrinda City. This research was conducted from May 2022 to April 2023 at UMKM Crab Food MC. The sample size is 21 respondents using purposive sampling and accidental sampling methods. The results of the study show that MSME Crab Food MC has been quite effective in implementing the 7p marketing mix marketing concept well. The variables that are already good include product, price, promotion, process and people or 5P which have been maximally carried out by MSME Crab Food MC. In addition, variables that must be improved include place variables, and physical condition variables, (2p) as well as being more creative in promoting existing products. This is based on the results of a simple SWOT analysis of marketing mix variables. Therefore the owner can increase marketing mix variables that are not yet optimal so that MSME Crab Food MC can develop better and get maximum profits